How stable is your customer? Individual and ipsative consistency of consumers' Big Five personality traits - Stefan Poier (Contemporary Economics, 2022)
In purchase behavior research, the personal dispositions of consumers can play a decisive role. This becomes relevant especially in very narrow target groups when socio-demographic constraints are very similar. In the present study, three types of continuity and change in the Big Five personality traits are investigated. While the Big Five personality traits have been extensively studied at the population level over the last decades, there is very little research at the individual level. This study is intended to fill the gap by investigating individual change and ipsative stability using representative panel data. Across four assessments, separated by four years, of the German Socio-Economic Panel (SOEP) from 2005 to 2017, a total of 58,502 participants (ages 16-103, 53% female) completed a 16-item personality short test. An exploratory structural equation analysis revealed very good model fit over age in all four observations. Individual change of a trait is examined by Asendorpf's IS indicator while ipsative stability is measured by the double-entry intra-class correlation coefficient. The results showed that in both domains, stability showed an inverse u-shape with a peak between the ages of 40 and 50.
Keywords: D11; D91; M31; 330; big five; ipsative consistency; individual stability; consumer behavior